1995
DOI: 10.1002/polb.1995.090331114
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic mechanical properties of ionomer/ionomeric microbead composites

Abstract: JOJ 1 RO SYNOPSISComposites of sulfonated polystyrene (PS-SSA) (0-8 mol % sulfonation) mixed with submicronic styrene-4 vinylpyridine (PS-4VP) (31 mol % 4VP content) microspheres were investigated by differential scanning calorimetry, Fourier transform infrared spectroscopy, and dynamic mechanical spectroscopy at 1 Hz in the glass transition region. The resulting proton transfer reaction from the SSA to the 4VP units was confirmed by IR spectroscopy, and led to a significant increase in the post-T, Young's mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…As a result, no absorption of the cyano group was found in the modified AS resin. It was also confirmed that the benzene ring in the styrene group was sulfonated to introduce a sulfonic acid group of 1034–1145 cm −11 18–20…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…As a result, no absorption of the cyano group was found in the modified AS resin. It was also confirmed that the benzene ring in the styrene group was sulfonated to introduce a sulfonic acid group of 1034–1145 cm −11 18–20…”
Section: Resultsmentioning
confidence: 89%
“…It was also confirmed that the benzene ring in the styrene group was sulfonated to introduce a sulfonic acid group of 1034-1145 cm 211 . [18][19][20] Figure 3 shows the reaction formula of the chemical modification of the waste AS resin using heated high-concentration sulfuric acid. The cyano group of acrylonitrile in the waste AS resin is converted into amide groups and carboxyl groups by hydrolysis, and a sulfuric acid group is introduced into the benzene ring in styrene by sulfonation.…”
Section: Resultsmentioning
confidence: 99%
“…The sulfonic acid and the sulfonate groups in the sulfonated waste polystyrene were confirmed by Fourier transformation infrared spectrum (FT-IR) measurement ,, and FT-NMR measurement . The percentage sulfonation was calculated by titration with NaOH solution against phenolphthalein indicator.…”
Section: Methodsmentioning
confidence: 99%
“…34 Compared to spectrum a, the appearance of a band at 1638 cm À1 in spectrum c is attributed to the formation of a protonated pyridinium group. 37,38 The bands at 1604 and 1420 cm À1 in spectra b and c are attributed to unsaturated stretching vibrations of CQC bonds and stretching vibrations of C-N groups, respectively. The weak band at 1218 cm À1 responds to the stretching vibrations of the N-O bond possibly derived from a partially oxidized pyridine group.…”
Section: Characterization Of C@p4vp-au Microspheresmentioning
confidence: 99%